Some problems of protection of architecture objects in the so-called “nadświdrzański style” - Krajewski, Adam (Budownictwo i Architektura / Civil and Architectural Engineering, 2015)
The paper contains a definition trial of wooden architecture objects in so-called. nadświdrzański style (popularly known as "świdermajer") in the area of vernacular architecture. Discussed were issues of sustainability materials and construction solutions in terms of the occurrence of degradation factors of wood in Poland and the solutions currently used in wooden constructions. Also analyzed ware some discrepancies in realities of residens initially using wooden buildings built in the so-called nadświdrzański style and contemporary standards for housing and recreation on the background of the region’s population changes Otwock / Wawer- region. The paper also addresses functioning attempts to preserve the architectural tradition so-called nadświdrzański style.